Makna Perpisahan dan Penerimaan pada Lirik Lagu “Selamat (Selamat Tinggal)” Karya Virgoun: Analisis Semiotika - Sahwa Laily; Dwi Wahyu Candra Dewi (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2025)
This study discusses the meaning of separation and acceptance in the lyrics of the song “Congratulations (Goodbye)” by Virgoun feat. Audy through Ferdinand de Saussure’s semiotic approach. Lyrics are not just a series of words, but contain symbols, hidden meanings, and emotional messages that can be interpreted in depth. Using an interpretive qualitative method, this study analyzes the relationship between the signifier and the signified in each verse of the song. The results of the analysis show that each verse represents the stages of emotion experienced by the character in the song, from nostalgia, loss, to acceptance and self-transformation. This song is not only about separation, but also describes the emotional maturity that arises from wounds and learning. The findings of this study indicate that symbols in the lyrics are able to convey universal messages about love, loss, and sincerity. The implications of this study indicate that song lyrics as a medium of symbolic communication can be a means of emotional reflection for listeners.